Enhancing Household Well-being through Zakat Assistance - Mohamed Saladin Abdul Rasool; Siti Nurul Akma Ahmad; Siti Mariam Ali (International Journal of Zakat, 2020)
The main purpose of Islam is to ensure and promote the wellbeing of all humanity and to avoid harm. From an Islamic perspective, wellbeing is explained through inside and outer fulfillment, driving towards a peaceful life, named as Hayat-e-Tayyaba. The objectives and vision of wellbeing are to satisfy the material and non-material needs. The Maqasid al-Shari’ah principles are normally used by scholars to explain wellbeing from the Islamic perspective. The objective of this empirical paper is to determine the wellbeing status of zakat recipient in Selangor using one of the dimensions of Maqasid al-Shari’ah that is wealth. Specifically, the potential ability of zakat to enhance the wellbeing of poor households is discussed. The present study employed a dataset derived from a survey consisting of 258 heads of households of poor zakat recipients in the state of Selangor, the most populated state in Malaysia. The cross-section study employed the proportionate random sampling method across nine districts in Selangor. The paper presents the wellbeing of households proxied by selected variables representing the five dimensions of Maqasid al-Shari’ah using descriptive statistics, T-test and Pearson correlation. In brief, the role of zakat to promote a better life from a micro perspective is highlighted.